Hepatitis C Prevalence, Incidence, and Treatment in Chinese Hemodialysis Patients: Results From the Dialysis Outcomes and Practice Patterns Study-China (2019–21) - Gan, Liangying; Wang, Dongyu; Bieber, Brian; McCullough, Keith; Jadoul, Michel; Pisoni, Ronald L.; Hou, Fanfan; Liang, Xinling; Ni, Zhaohui; Chen, Xiaonong; Chen, Yuqing; Zuo, Li (Frontiers in Medicine, 2022)
Background: Prior work from the Dialysis Outcomes and Practice Patterns Study (DOPPS) showed HCV prevalence in China in 2012-2015 being in the upper third and HCV incidence the 2nd highest among 15 different countries/regions investigated. The goal of the present investigation was to: (1) determine if HCV prevalence and incidence has changed, and (2) collect detailed data to understand how HCV is treated, monitored, and managed in Chinese HD facilities and non-dialysis chronic kidney disease (CKD) clinics. Data & Methods: Detailed data for 1700 randomly selected HD patients were reported by 39 randomly selected HD facilities from Beijing, Shanghai, and Guangzhou participating in the DOPPS 7-China study from 2019-2021. The study site medical directors completed a survey regarding numerous aspects of HCV treatment and management in HD and ND-CKD patients. Results: In this 2019-2021 cohort, HCV prevalence was 7.4%, which was lower than the 14.8% and 11.5% HCV prevalence for the 2009-2011 and 2012-2015 cohorts, respectively. HCV incidence of 1.2 cases per 100 pt-yrs also was lower compared to the incidence of 2.1 for the 2012-2015 cohort. Although the great majority of study site medical directors indicated that all or nearly HCV+ patients should be treated for their HCV, very few HCV+ patients have been treated presumably due to substantial cost barriers for affording the new direct acting antivirals (DAAs). The randomly selected facilities in our DOPPS 7-China study appear to have excellent programs in place for frequent monitoring of patients and staff for HCV, education of staff, and referral of HCV cases to external infectious disease, gastroenterology, and liver disease specialists. Liver biopsies were not commonly performed in HCV+ HD patients. HCV genotyping also was rarely performed in participating units. Conclusions: Our study indicates a 50% decline in HCV prevalence and a >40% decline in HCV incidence in Chinese HD patients over the past 10-12 yrs. Chinese HD facilities and associated specialists appear to be well equipped and organized for successfully treating and managing their HCV+ HD and CKD patients in order to achieve the WHO goal of eliminating HCV by 2030.